1972
DOI: 10.1063/1.1678353
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence of Zinc Oxide Crystals Controlled by Electrode Potential and Electrochemical Reactions

Abstract: The voltage dependence of the green luminescence of ZnO crystals used as electrodes in an electrochemical cell was investigated and compared with the voltage dependence of the photocurrent. When the exciting light is of shorter wavelength than the band edge of ZnO, this luminescence can be varied from its maximal value to complete extinction by applying small positive voltages. The luminescence resulting from excitation within the long wavelength tail of absorption, however, cannot be influenced. The potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1975
1975
1997
1997

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In addition, the results of electrical and optoelectrical admittance spectroscopy show that surface recombination plays an important role; the difference between j/eφ and 1 -I/I M is the recombination current density j r divided by eφ. As a consequence, the claim, made in ref 17, that the luminescence vs potential and the photocurrent quantum yield vs potential measurements are fully complementary, is not correct.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, the results of electrical and optoelectrical admittance spectroscopy show that surface recombination plays an important role; the difference between j/eφ and 1 -I/I M is the recombination current density j r divided by eφ. As a consequence, the claim, made in ref 17, that the luminescence vs potential and the photocurrent quantum yield vs potential measurements are fully complementary, is not correct.…”
Section: Discussionmentioning
confidence: 97%
“…Light emission from ZnO photoanodes has been observed in the potential range in which holes recombine with majority carriers. , Since it is generally agreed that surface recombination is nonradiative, photoluminescence indicates that at least a part of the photogenerated holes recombine in the bulk solid. Petermann et al claimed a strict correlation between the photocurrent and the green luminescence at ZnO single-crystal electrodes. This result indicated that photoluminescence might be a useful tool for the study of the competition between bulk recombination and anodic charge transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The effects which the passage of photocurrent has on PL properties have been examined with a number of n-type semiconductors exhibiting edge emission and/or impuritybased subband-gap emission. The former category includes ZnO and CdS.,-Sei-x (0 < .v < 1) samples; in the latter category are Cu-doped ZnO (ZnO:Cu) and CdS:Te (8)(9)(10)(11). In all cases examined, passage of anodic photocurrent from ultraband-gap excitation quenched the PL intensity but did not appreciably alter the spectral distribution.…”
Section: Propertiesmentioning
confidence: 95%
“…The luminescence properties of the semiconductor/electrolyte solution interface are known to provide useful information of the mechanism of electrochemical reactions as well as the potential distribution at the interface .…”
Section: Introductionmentioning
confidence: 99%